Analisis Pemanfaatan Pengguna Transaksi Online (E-commerce) di Kalangan Masyarakat - Tamamil Asna, Naila; M. Arif Kurniawan; Nur Fani Arisnawati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research aims to analyze the use of the Paesan village community regarding e-commerce. This research uses qualitative research methods with secondary data collection methods. Primary data was taken from interviews with the community and observations at the research site. The research results showed that E-commerce (Online Transactions) is quite helpful for people in making transactions. And the clarity of the information obtained so that the public, the respondents, acknowledged that the existence of this system was only to make things easier. The benefits obtained from this system are numerous. Because the online transaction system helps people who, if they forget to bring cash, can use online transactions using technological media. With this system, people who have difficulty understanding technology are not jealous of the existence of this system. So that people now avoid the word technologically ignorant.